A study using two methods to examine a skin layer called the upper basket‐weave pattern layer. (1st February 2020) - Goto, H.; Tada, A.; Ibe, A.; Kitajima, Y.
Summary: The skin is made up of several layers, the very outermost of which is the stratum corneum. The normal stratum corneum (SC) itself has two layers, an upper basket‐weave (B‐W) pattern layer and, below this, a lower compact layer. Corneodesmosomes are cells found in the stratum corneum, and in healthy skin, their number decreases (the cells degrade) from the lower compact layer up to the upper basket‐weave pattern layer, and their distribution (layout) changes. This can be seen by a process that looks at levels of desmoglein 1 (Dsg1) in skin cell samples taken on sticky tape (tape stripping), as levels of Dsg1 represent the numbers of corneodesmosomes. In some skin diseases such as ichthyosis vulgaris and X‐linked ichthyosis, there is no basket‐weave pattern layer, or it is incomplete. In this study, the function of the upper basket‐weave pattern layer was explored, using reconstructed human epidermis (RHE, a type of model of skin developed from skin cells) as well as skin cells taken from female volunteers by tape stripping. The scientists used an oil‐in‐water emulsion, prepared cream‐A, and successfully generated the upper basket‐weave pattern layer in reconstructed human epidermis in which the degradation of corneodesmosomes was promoted. This could be a useful tool for investigating the physiological significance of the basket weave layer in vitro (meaning in the lab rather than on humans). Using the cells from the female volunteers, the researchers found that degradation of Dsg1 in the outermost stratum corneum, which represents the basket‐weave pattern layer forming, was correlated with water‐barrier functions (a sign of a healthy skin barrier) and the SC softness of healthy skin, which varied widely. Being able to measure Dsg1 content in the stratum corneum obtained by tape‐stripping from human skin, can make it possible to study the effects of external stimulants, such as creams/ointments, on the completeness of the basket weave layer without the need for a biopsy. This summary relates to the study: Basket‐weave structure in the stratum corneum is an important factor for maintaining the physiological properties of human skin as studied using reconstructed human epidermis and tape stripping of human cheek skin